Mekanisme Pelayanan Rumah Singgah Untuk Pasien Rujukan Oleh Dinas Kesehatan Provinsi Gorontalo - Ismail, Fitra; Rachman, Ellys; Thalib, Tety (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
This study aims to determine and analyze the mechanism of shelter home services for referred patients organized by the Gorontalo Provincial Health Office. The focus of the study is how the stages of registration, completeness of files, and implementation of surveys on patients referred outside the region using descriptive qualitative methods with data collection techniques through interviews, observations, and documentation. Informants in this study consisted of Health Office officials, shelter home officers, and patients and families of patients who use the service.The results of the study indicate that many people do not clearly understand the registration procedure and the completeness of the required files, which causes obstacles in the service process. In addition, it was found that the patient eligibility survey process had not been running effectively, especially in terms of assessing economic and health feasibility. This study recommends the need for increased socialization regarding the shelter home service mechanism, simplification of registration procedures, and periodic evaluation of the performance of shelter home services to ensure the effectiveness and efficiency of services.